Faktor-Faktor yang Mempengaruhi Pemilihan Lokasi Industri Era Revolusi Industri 4.0 di Kawasan Kota Makassar - Syamsu Rijal (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2021)
The world continues to change, entering the era of Industry 4.0 or the Fourth Global Industrial Revolution, where information technology has become the foundation of human life. The difference in the characteristics of the industry with the industry in general raises the possibility that the classical theory of industrial position is not suitable to be applied to the digital creative industry. The purpose of this study is to determine the factors that influence the selection of industrial locations in the era of the industrial revolution 4.0 in the city of Makassar. The research method used is descriptive research with a qualitative approach. Descriptive method by describing or describing the current state of the research subject based on current events or the status quo. Several factors that influence the selection of digital creative industry locations that are not included in the proposal are: (1) quiet and comfortable conditions, (2) the strength of internet availability, (3) accessibility and (4) traffic accessibility. Factors that are consistent with the general proposal are the availability of labor and the availability of infrastructure, and more specifically the location of raw materials, transportation costs, and land prices. Factors that are not in accordance with the proposal are the location near the market and industrial concentration areas. The unique characteristics of the digital creative industry are different from the industry as a whole, which influences various considerations in choosing a business location due to the influence of information technology.